Studying the Influence of some Technological Factors on the Properties of Nitrocellulose-cellulose Material Sheets - Khuong, Pham Van; Vu, Hoang The; Huu, Ngo Van; Tuong, Nguyen Manh (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 2DO - 10.25073/2588-1140/vnunst.5766, 2024)
This study presents the results of manufacturing cellulose-cellulose nitrate materials using paper-making equipment in the laboratory Rapid-Kothen. Determine the influence of the ratio of components, pulp grinding, additives, and lamination technology on the properties of cellulose-cellulose nitrate materials. Using chemical analysis, the technical specifications of some UKP pulps were analyzed and US softwood UKP pulps were selected for use in research. Through SEM images and experiments, it is shown that the morphology of NC greatly affects the remaining nitrate cellulose content in the material. NC-C material samples with different mixing ratios, using pulp with different grinding degrees were also investigated for mechanical properties and the degree of preservation of materials on the mesh. The influence of additives such as cationic starch and carboxymethyl cellulose (CMC) on the mechanical properties of the material was also investigated. Lamination using nitrate cellulose glue or alcohol:ether solvent mixture can significantly increase the mechanical properties of the material.